2019
DOI: 10.24036/00191za0002
|View full text |Cite
|
Sign up to set email alerts
|

Why Victims of Domestic Violence Still Survive Their Marriage? Preliminary Analysis of Forgiveness Dynamics Conditions

Abstract: The purpose of this study was to find out how the dynamics of forgiveness of domestic violence victims. Anything that is the reason for the victim chooses to provide forgiveness and maintain the relationship of his household. The method used in this article is the library research method. The results of this study indicate that victims of domestic violence choose to provide forgiveness because it is influenced by certain factors. This factor becomes a force of the victim to maintain his household relationship.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These findings answered the second and third research questions. Studies reveal that women who are victims of domestic violence forgive their spouses in the face of violence for the continuation of their marriage (Afdal, Sari, et al., 2019; Alan et al., 2016b; Sartika & Amalia, 2014). Sartika and Amalia (2014) found that 73% of the women who were victims of violence forgave their spouses in order to save their marriage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings answered the second and third research questions. Studies reveal that women who are victims of domestic violence forgive their spouses in the face of violence for the continuation of their marriage (Afdal, Sari, et al., 2019; Alan et al., 2016b; Sartika & Amalia, 2014). Sartika and Amalia (2014) found that 73% of the women who were victims of violence forgave their spouses in order to save their marriage.…”
Section: Discussionmentioning
confidence: 99%
“…In patriarchal societies like Turkey, the reasons why women continue to stay together with their partners despite violence are generally economic reasons, presence of children, social pressure, and internalization of violence (Alan et al., 2016a, 2016b; Dikmen & Munevver, 2020; Hacettepe University, Institute of Population Studies, 2014). In a study conducted in Indonesia, it was reported that women subjected to violence forgive their partners and continue their relationship, due to several reasons such as shame, lack of an income‐generating job, and the presence of children, reasons similar to the ones reported in Turkey (Afdal, Arnaldi et al, 2019, & Afdal, Sari, et al, 2019). Furthermore, in a study, a high tendency to forgive individuals was found to be associated with high psychological resilience (Kravchuk, 2021).…”
Section: Introductionmentioning
confidence: 94%
“…Social support can be said to be a key variable associated with optimal adjustment even for chronic diseases [36]. One indication that causes postpartum rage in young mothers is the lack of social support provided by family members [9], [37]. The emergence of postpartum rage in young mothers creates powerlessness in young mothers.…”
Section: Introductionmentioning
confidence: 99%